Evaluation of fine needle aspiration biopsy as a diagnostic tool in pediatric head and neck lesions - Deepti Agarwal; Suprabha Sharma; Shyamoli Dutta; et al (Dove Medical Press, 2010)
Deepti Agarwal1, Suprabha Sharma2, Shyamoli Dutta1, Rani Bansal2, Seema Awasthi1, Anjali Khare2, Maryem Ansari11Department of Pathology, Teerthanker Mahaveer Medical College, Moradabad, India; 2Department of Pathology, Subharti Medical College, Meerut, IndiaBackground: Fine needle aspiration (FNA) biopsy is a well accepted diagnostic procedure and considered to be a valuable test for initial assessment of head and neck swellings in adults. The technique has gained popularity in the pediatric population over the last decade, with varying degrees of acceptance rates, accuracy, and results among pathologists.Objective: This study was performed to evaluate the utility of aspiration cytology as a first-line diagnostic tool in palpable head and neck masses in children, taking into account the diversity of lesions observed in this subset of the population. Cytologic analysis was correlated with histologic results for evaluating diagnostic accuracy wherever possible. The applicability of FNA biopsy in diagnosing pediatric malignant lesions was also evaluated.Methods: This retrospective study conducted from January 2008 to December 2009 screened all pediatric cases referred to the departments of pathology at two tertiary care hospitals in India. Data from a total of 662 children aged 0–15 years presenting with head and neck masses who underwent FNA biopsy were collected. Cytologic results were interpreted and analyzed according to anatomic site. The lesions were then categorized into inflammatory, infective, and neoplastic.Results: Of the 662 lesions, 23 cases were excluded due to inadequate material, thus the data for 639 cases were finally evaluated. Lymph node lesions predominated, accounting for 570 cases (89.2%), of which 412 (72%) cases were diagnosed as reactive and 91 (16%) cases as tubercular lymphadenitis. Other lesions aspirated were thyroid (18 cases, 2.8%), salivary gland (12 cases, 1.8%), and miscellaneous surface lumps (39 cases, 6.1%). Of all the cases, 628 (98.27%) were reported as benign and 11 (1.67%) as malignant. The positive predictive value of cytologic analysis in diagnosing malignancy was 100%, although exact typing of lesions was possible only on histopathologic examination.Conclusion: FNA biopsy is a sensitive and minimally invasive first-line investigation in the diagnosis of head and neck masses in children. It is highly accurate in isolating and determining potentially neoplastic lesions, thus guiding the way for cases which truly require excision biopsy or other second-line investigations.Keywords: fine needle aspiration, biopsy, tubercular, lymphadenopathy, thyroid